A Year with the Sages : Wisdom on the Weekly Torah Portion - Hammer, Reuven (Book collections on Project MUSE., 2019)
"A Year with the Sages relates the Sages' understanding of individual Torah portions to contemporary life situations. Quoting from the week's portion, Rabbi Reuven Hammer presents a Torah commentary, sayings from the Sages, a commentary elucidating these concepts and their consequences, and a reflection illuminating the Sages' wisdom for our era."--